2015
DOI: 10.3402/fnr.v59.29733
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment methods for zinc supplementation in prepubertal non-zinc-deficient children

Abstract: BackgroundZinc is an essential nutrient that is required for numerous metabolic functions, and zinc deficiency results in growth retardation, cell-mediated immune dysfunction, and cognitive impairment.ObjectiveThis study evaluated nutritional assessment methods for zinc supplementation in prepubertal non-zinc-deficient children.DesignWe performed a randomised, controlled, triple-blind study. The children were divided into a control group (10% sorbitol, n=31) and an experimental group (10 mg Zn/day, n=31) for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Giving a dose of 5 mg for 2 weeks at under 2 years significantly zinc plasma levels better than placebo [25]. Giving a dose of 10 mg/day for 3 months in children showed that there was a significant increase in serum zinc in the intervention group [26].…”
Section: Discussionmentioning
confidence: 91%
“…Giving a dose of 5 mg for 2 weeks at under 2 years significantly zinc plasma levels better than placebo [25]. Giving a dose of 10 mg/day for 3 months in children showed that there was a significant increase in serum zinc in the intervention group [26].…”
Section: Discussionmentioning
confidence: 91%
“…The PA is an indicator of change in the integrity of cell membranes and the intercellular space (23). Lopes et al (24) reported a mean PA of 5.0° in the healthy population. In our study, we observed lower values of 3.0° and 2.4° for G1 and G2, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Zn-NPs also affect molecular signaling pathways and stimulate both different metabolic effects in distinct organisms [53] and innate immune systems [54]. Zinc has also been shown to improve both weight and height development in humans [55]. Therefore, Zn-NPs favored a growth increase.…”
Section: Discussionmentioning
confidence: 99%